Preconditions of Infrastructure Development of Cooperative in Agriculture - Ramanauskas, Julius (Ekonomika, 2000)
Some aspects of the results of agricultural land reform in Lithuania are given in this paper. The privatization of the agricultural infrastructure is shown as very detrimental to the farmers. Many enterprises of production, services and trade, that render services to the farmers remained the monoppolists in the most aspects. The methods of the anticipation of the cooperative activity, that enable the members of the cooperatives to see its merrits and to make the decision to take part in its activity.